Technical analysis for dummies - Rockefeller, Barbara 1946- (Wiley, 2011)
A simple, straightforward guide to the fundamentals of technical analysis, giving you plain-English explanations on everything you need to know to put money in a securities market to astounding results.
Includes bibliographical references and index. - Print version record
Keywords: Investment analysis; Technical analysis (Investment analysis); Analyse technique (Analyse financière); Analyse financière; BUSINESS & ECONOMICS; Investments & Securities